2020
DOI: 10.1097/spc.0000000000000494
|View full text |Cite
|
Sign up to set email alerts
|

Breakthrough cancer pain in 2020

Abstract: Purpose of the review: An overview on breakthrough cancer pain (BTCP), including inherent limitations of the terminology, assessment, clinical presentation, and treatment options.Recent findings: The estimated prevalence of BTCP is dependent on the defined cutoffs for controlled background pain and the magnitude of the pain flare. In addition, pain flares outside the definition of BTCP are prevalent. In the 11th Revision of the International Classification of Diseases (ICD-11), the temporal characteristics of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Breakthrough cancer pain (BTcP) is a heterogeneous construct whose definition is far from clearly established [ 1 ]. However, it is generally accepted that BTcP includes two main components, namely (i) the presence of controlled baseline oncological pain and (ii) a transient exacerbation of this pain [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Breakthrough cancer pain (BTcP) is a heterogeneous construct whose definition is far from clearly established [ 1 ]. However, it is generally accepted that BTcP includes two main components, namely (i) the presence of controlled baseline oncological pain and (ii) a transient exacerbation of this pain [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, BTcP was recently defined as a severe pain episode of short duration (usually less than 30 min) in patients who are receiving stable opioid-based analgesics for baseline pain, which is described as mild to moderate in intensity (i.e., under four points in a numerical rating scale from 0 to 10) [ 4 ]. According to its triggering factors, BTcP could be classified as incidental (predictable: provoked by voluntary movements such as walking; unpredictable: provoked by involuntary reactions such as swallowing or intestinal distension) or spontaneous (i.e., without a clear trigger) [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several pieces of evidence showed that BTcP cannot be intended as a single nosological entity but includes different and changing pathogenetic mechanisms justifying its sub-typing [7,9,17]. Consequently, methods useful for dissecting the NP-BTcP forms can offer great help for clinicians and important benefits for patients [18].…”
Section: Discussionmentioning
confidence: 99%
“…Bone pain due to metastases is the most common symptom demanding treatment in oncological patients [1]. Beside the pain, bone metastases (BM) can cause spinal cord compression, pathological fractures, and hypercalcemia [2].…”
Section: Introductionmentioning
confidence: 99%